The Anatomy of Constitution Making: From Denmark in 1849 to Iceland in 2017 - Thorvaldur Gylfason (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper reviews aspects of the constitution making process in Iceland after the financial collapse of 2008, emphasizing the differences between the provisional constitution of 1944 when Iceland separated unilaterally from Nazi-occupied Denmark and Denmark's 1849 constitution which served, with notable exceptions, as the prototype for Iceland's 1944 constitution. The comparison and contrast between the Icelandic and Danish constitutions invites a comparison also between Iceland's 1944 constitution with the new post-crash constitution from 2011 accepted by two thirds of the voters in a national referendum in 2012 and waiting to be ratified twice by a reluctant Parliament. Against this comparative background, the paper proceeds to discuss political and procedural aspects of Icelands constitutional reform project, and concludes by proposing lessons to be learned from Icelands experience thus far.
Keywords: K10; 330; constitution making; democracy; Iceland; Denmark